2010
DOI: 10.1080/00063650903431654
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal distribution of Southern Grey ShrikesLanius meridionalisin agricultural areas

Abstract: Capsule Southern Grey Shrikes were spatially segregated by sex during the non-breeding period. Aims To provide data that show sex-related spatial segregation in Southern Grey Shrikes in agricultural areas and suggest possible causes. Methods Shrikes were captured using a modified potter trap in a 169-km 2 study area in the Duero River valley, western Spain, which encompassed areas of irrigated and non-irrigated crop lands. Birds were sexed and colour-ringed, and capture locations and re-sighting locations plot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
(7 reference statements)
1
4
0
Order By: Relevance
“…On the other hand, we can discard the idea that the local‐resource‐competition hypothesis rules the sex ratio in southern shrikes. We found evidence that females are the dispersing sex in the southern shrike, as in most of birds (Clarke et al ; also see Campos and Martín ). Therefore, this hypothesis would predict just the opposite of what we found, that is, in bad years for breeding or in broods reared by low‐quality parents, the sex ratio would be biased to the more dispersing sex, in order to decrease future local competition – i.e.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…On the other hand, we can discard the idea that the local‐resource‐competition hypothesis rules the sex ratio in southern shrikes. We found evidence that females are the dispersing sex in the southern shrike, as in most of birds (Clarke et al ; also see Campos and Martín ). Therefore, this hypothesis would predict just the opposite of what we found, that is, in bad years for breeding or in broods reared by low‐quality parents, the sex ratio would be biased to the more dispersing sex, in order to decrease future local competition – i.e.…”
Section: Discussionsupporting
confidence: 71%
“…Beyond a descriptive study, our main goal is to discern between the cost‐of‐reproduction hypothesis and the local‐resource‐competition hypothesis as explanations for biased sex ratios associated with harsh conditions for breeding. Southern shrike constitutes an ideal model study for discerning between these two hypotheses because: 1) as in most of passerines, females are the dispersing sex (Campos and Martín ), but 2) in contrast with most of passerines, males are not heavier than females (Gutiérrez‐Corchero et al , ); and, in fact, we found evidence for females being more costly to rear than males (Results). This gives us a valuable opportunity for discerning between the two hypotheses.…”
mentioning
confidence: 66%
“…Irrigated crops are located closer to the river Duero and their degree of humidity is higher, which should favour the presence of vectors that transmit haemoparasites. Moreover, Southern grey shrike females move to irrigated areas at the end of the breeding season (Campos & Martín 2010) but, surprisingly, they were not found to be more infected than males.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the knowledge of the sex of the birds studied is often essential given that individual discrimination is required in order to analyze their behaviour, etc. Spatial sexual segregation has been analysed in many bird species, mainly during the breeding season (see review of Catry et al, 2005), but also at other seasons (Campos & Martín, 2010). This raises the issue of which sex is the dominant one in each species and which habitat requirements has each sex through the annual cycle.…”
Section: Sex Determinationmentioning
confidence: 99%
“…An example based on the Southern grey shrike shows the different conclusions reached using one method or another. The Southern grey shrike is a medium size bird (25 cm) whose sexes remain separate during the non-breeding period: males remain in the breeding territories and females occupy distant areas (Campos & Martín, 2010). Campos et al (2008) analysed the seasonal variation in the relationship body size -body mass in agricultural areas of Northern Spain, separating males and females.…”
Section: Body Size -Body Mass Relationshipmentioning
confidence: 99%